Little house on the prairie - Wilder, Laura Ingalls, 1867-1957 (Little house, 2007)
The Ingalls family travels from the big woods of Wisconsin to a new home on the prairie, where they build a house, encounter Native Americans, dig a well, and fight a prairie fire.